2000
DOI: 10.1046/j.1365-2249.2000.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD30 is more relevant to disease activity of atopic dermatitis than soluble CD26

Abstract: SUMMARYIt is suggested that CD30 and CD26 are surface molecules expressed on activated Th2 and Th1 cells, respectively. We examined plasma levels of soluble CD26 (sCD26) and sCD30 in patients with atopic dermatitis (AD) when their eruptions were aggravated and in non-atopic healthy controls, and then analysed the possible correlation between these values and the levels of several clinical markers. The plasma levels of both sCD30 and sCD26 were significantly higher in AD patients than in controls, both in exace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 35 publications
(44 reference statements)
2
34
1
Order By: Relevance
“…9 Conversely, corticosteroids suppress inflammation by inhibiting the action of nuclear factor-kB. 10 Consistent with that, and in line with previous intervention studies, 1,5 the decrease in serum sCD30 seen in our study was linked to the concurrent improvement of lung function, especially in children with atopy who received inhaled budesonide.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…9 Conversely, corticosteroids suppress inflammation by inhibiting the action of nuclear factor-kB. 10 Consistent with that, and in line with previous intervention studies, 1,5 the decrease in serum sCD30 seen in our study was linked to the concurrent improvement of lung function, especially in children with atopy who received inhaled budesonide.…”
supporting
confidence: 91%
“…1,2 In contrast, sCD26 has been found to be inversely associated with disease severity in patients with chronic eosinophilic pneumonia. 3 Increased levels of sCD30 in serum samples have been found in patients with atopic dermatitis, 4 and an association between elevated sCD30 and the severity of eczema has been observed.…”
mentioning
confidence: 95%
“…19,29 A correlation between sCD30 levels and disease activity has also been reported in patients with atopic dermatitis and in asthma. 28,30 An inverse correlation of sCD26 with disease activity has been reported in patients with systemic lupus erythematosus and anti-neutrophil cytoplasm antibody-associated vasculitides. 21,31 We have shown elevated levels of sCD26 and sCD30 in individuals infected with Leishmania infantum.…”
Section: Discussionmentioning
confidence: 96%
“…High levels of both sCD26 and sCD30 have been reported in atopic dermatitis which is a Th2-related chronic inflammatory skin disease. 28 It seems that in skin inflammatory diseases the sCD26 level in plasma is less representative marker for Th1-dominated response or disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Latest reports indeed investigated the Th1/Th2 balance during several diseases by analysis of the serum sCD26 and sCD30 levels [31, 32, 33]. Recently, it was concluded that CD26 upregulation may be suggestive of Th1-like immune reactions and that the release of sCD26 correlates with cell surface CD26 expression [10, 11, 34].…”
Section: Discussionmentioning
confidence: 99%